Insect Physiology and Ecology - Shields, Vonnie D.C (IntechOpen, 2017)
This book discusses recent contributions focusing on insect physiology and ecology written by experts in their respective fields. Four chapters in this book are dedicated to evaluating the morphological and ecological importance and distribution of water beetles, dung beetles, weevils, and tabanids, while two others investigate the symbiotic relationships between various insects and their associations with bacteria, fungi, or mites. Two other chapters consider insecticide detoxification, as well as insect defense mechanisms against infections. The last two chapters concentrate on insects as sustainable food. This book targets a wide audience of general biologists, as well as entomologists, ecologists, zoologists, virologists, and epidemiologists, including both teachers and students in gaining a better appreciation of this rapidly growing field.